Sampling Theory and Practice - Murphy, Casey (USA : Willford Press, 2024)
Sampling Theory and Practice.Statistics is an integral part of mathematics. It encompasses the handling of data through tasks such as data collection, presentation, interpretation, analysis, and organization. Within statistics, sampling theory refers to the survey method in which a particular group of people are chosen to represent the larger population. This is a very common method used in marketing and research. Various sampling methods include theoretical sampling, cluster sampling, snowball sampling, systematic sampling, stratified sampling. minimax sampling, and others. The topics included in this book on sampling theory are of utmost significance and bound to provide incredible insights to readers. It includes topics that deal with the basic to the most complex concepts and approaches of this area. It aims to serve as a resource guide for students and facilitate the growth of the discipline.
Includes index.
Keywords: Sampling Statistics; Cluster sampling; Nonprobability